Komposisi Musik Bola Bekel dan Kerang - A’rifah, Yulia Fatwa; Setiaji, Denden (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
This study aims to investigate the possibility of using sounds produced from traditional Indonesian games, namely bola bekel and shells, as the main material in the creation of modern musical works. With an exploratory and experimental approach, this work combines elements of children's play and the richness of the coastal environment as part of the acoustics and story. The creation process includes sound experiments through reflections, tapping, and friction on these objects with various media, while processing the symbolic and cultural values contained. The end result is music that not only provides a special listening experience, but also serves as a means of preserving regional culture and educating artists. It is hoped that this work will inspire the emergence of new forms of composition that focus on exploring everyday objects and traditional values.